IMMU-03. UPDATES ON BRAINCHILD-01, -02, AND -03: PHASE 1 LOCOREGIONAL CAR T CELL TRIALS TARGETING HER2, EGFR, AND B7-H3 FOR CHILDREN WITH RECURRENT CNS TUMORS AND DIPG. (4th December 2020) - Vitanza, Nicholas; Gust, Juliane; Wilson, Ashley; Huang, Wenjun; Perez, Francisco; Wright, Jason; Leary, Sarah; Cole, Bonnie; Albert, Catherine; Pinto, Navin; Orentas, Rimas; Jensen, Michael; et al.
Abstract: We report preliminary results of three Phase 1 trials of repetitively dosed locoregional CAR T cells for children with recurrent/refractory CNS tumors, targeting HER2 (BrainChild-01), EGFR (BrainChild-02), and B7-H3 (BrainChild-03). Cells are delivered into the tumor cavity (Arm A) or ventricular system (Arm B and BrainChild-03's DIPG-specific Arm C). Primary endpoints are feasibility and safety. Successful CAR T cell manufacture occurred in 2/2 subjects (BrainChild-01) and 2/3 (BrainChild-02). All subjects tolerated intra-patient dose escalation from 1x10 7 to 2.5x10 7 cells/dose without DLTs. Two subjects were evaluable on BrainChild-01 (S-001: glioblastoma, Arm A, survival 173 days post-first infusion, received 6 infusions; S-002: ependymoma, Arm B, survival 111 days, 9 infusions). One subject was evaluable on BrainChild-02 (glioblastoma, Arm A, withdrew from trial at 49 days, 5 infusions). One enrolled patient on BrainChild-03 has not begun treatment. None of the subjects developed new neurologic toxicities, although transient worsening of baseline tumor-related signs and symptoms were seen. Secondary endpoints are efficacy and disease response. No objective radiographic responses have been observed. Both BrainChild-01 subjects had transient systemic CRP elevations following infusions (S-001: peak of 3.9 post Course 1 Week 1; S-002: peak of 2.3 post Course 2 Week 1), possibly indicating an inflammatory response. Both subjects had post-infusion CSF cytokine elevations (CXCL10, GCSF, GM-CSF, IFNa2, IFNg, IL-10, IL12-p40, IL12-p70, IL-15, IL-1a, IL-3, IL-6, IL-7, TNFa, VEGF) without concurrent systemic changes. In summary, we provide preliminary evidence of safety and feasibility of intracranial delivery of CAR T cells for pediatric CNS tumors.